2014
DOI: 10.1001/jamaoto.2014.2846
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Treatment of Lacrimal Gland Tumors

Abstract: Our study demonstrates that ACC is the most common malignant epithelial neoplasm of the lacrimal gland. Determinants of survival for tumors of the lacrimal gland include age at diagnosis and surgical therapy. Radiation therapy is associated with improved DSS in SCC but not in ACC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
55
0
1

Year Published

2014
2014
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(57 citation statements)
references
References 43 publications
1
55
0
1
Order By: Relevance
“…Application of the SEER database to analyze patient and diseaserelated characteristics has been previously validated in several studies investigating malignancies of the head and neck. [15][16][17][18][19][20] Surgery and early detection of maliginant odontogenic tumors significantly improve patient prognosis. However, no clear survival benefits were found for radiation therapy.…”
mentioning
confidence: 99%
“…Application of the SEER database to analyze patient and diseaserelated characteristics has been previously validated in several studies investigating malignancies of the head and neck. [15][16][17][18][19][20] Surgery and early detection of maliginant odontogenic tumors significantly improve patient prognosis. However, no clear survival benefits were found for radiation therapy.…”
mentioning
confidence: 99%
“…Most malignant lacrimal sac tumors are treated with surgery or radiotherapy, but there is no consensus for management due to its rarity [5]. A recent cohort analysis suggested that both surgery and radiotherapy improved survival in patients with SCC of the lacrimal duct [6]. However, while local invasion is common, metastases of lacrimal gland tumors are seldom reported [6].…”
Section: Discussionmentioning
confidence: 99%
“…A recent cohort analysis suggested that both surgery and radiotherapy improved survival in patients with SCC of the lacrimal duct [6]. However, while local invasion is common, metastases of lacrimal gland tumors are seldom reported [6]. One case series of 82 patients reported lymphatic metastases in 21 patients (26%), lung metastases in 4 patients and esophageal metastases in 2 patients [7].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…5,6 The data extracted from the Surveillance, Epidemiology, and End Results database show that the best relative survival of the common orbital neoplasms, including uveal melanoma, lacrimal gland tumor, and sinonasal malignancies with orbital involvement, was noted in patients treated with surgery or a combination of surgery and chemoradiotherapy. [7][8][9][10][11] Given the multidisciplinary medical advancements in treating orbital neoplasms, there is an increasing number of survivors who require surveillance imaging to monitor local disease control and treatment response, and to detect early recurrence and guide subsequent management. [10][11][12][13] Other common orbital procedures include orbital decompression for thyroid orbitopathy and maxillofacial orbital reconstruction in the setting of trauma.…”
Section: Introductionmentioning
confidence: 99%